Affordability of nutritious diets in rural India - Raghunathan, Kalyani; Headey, Derek D.; Herforth, Anna (Elsevier, 2021)
In 2015–16 some 38% of preschool children in India were stunted, 21% wasted, and more than half of Indian mothers and young children were anemic. Though widely studied, surprisingly little research on malnutrition in India explores the role of diets, particularly the affordability of nutritious diets given low wages and the significant structural problems facing India’s agricultural sector. To explore this we used nationally representative rural price and wage data to estimate the least cost means of satisfying India’s national dietary guidelines, referred to as the Cost of a Recommended Diet (CoRD), and assessed the affordability of this diet relative to male and female wages for unskilled laborers. Although we find that dietary costs have increased substantially for both men and women, rural wage rates increased more rapidly, implying that nutritious diets became substantially more affordable over time. However, in absolute terms nutritious diets in 2011 were still expensive relative to unskilled wages, constituting approximately 80–90% of female and 50–60% of male daily wages. Overall, we estimate that 63–76% of the rural poor could not afford a recommended diet in 2011. Achieving nutritional security in India requires a much more holistic focus on improving the affordability of the full range of nutritious food groups (not just cereals), a reappraisal of social protection schemes in light of the cost of more complete nutrition, ensuring that economic growth results in sustained income growth for the poor, and more timely and transparent monitoring of food prices, incomes and dietary costs.